Simulation studies of Sn-based perovskites with Cu back-contact for non-toxic and non-corrosive devices. Issue 16 (28th August 2019) - Ahmed, Saquib; Harris, Jalen; Shaffer, Jon; Devgun, Mohan; Chowdhury, Shaestagir; Abdullah, Aboubakr; Banerjee, Sankha
Abstract: Abstract : Using general-purpose photovoltaic device model, we have simulated the operation and functionality of a working Sn perovskite/Cu2 O hole transport layer (HTL)/Cu back-contact device versus a standard Pb perovskite/Spiro HTL/Ag back-contact device. The results are extremely promising in that they showcase comparable cell efficiencies, with the Sn perovskite/Cu2 O HTL/Cu back-contact device showing a highest 22.9% efficiency [ J sc of 353.4 A/m 2, V oc of 0.84 V, fill factor (FF) of 0.77] at 427 nm active layer thickness compared with 24.6% of the standard Pb perovskite/Spiro HTL/Ag back-contact device ( J sc of 356.8 A/m 2, V oc of 0.82 V, FF of 0.84) at the same active layer thickness. J sc, V oc, and FF kinetics reveal that the Sn perovskite/Cu2 O HTL/Cu back-contact device can perform better by reducing the recombination centers both within each layer matrix and in the interfacial contacts.